Enhanced multi-wavelength holographic profilometry by laser mode selection - Muramatsu, Mikiya (2006)
The application of multi-wavelength holography for surface shape measurement is presented. In our holographic setup a Bi12TiO 20 (BTO) photorefractive crystal was the holographic recording medium and a multimode diode laser emitting in the red region was the light source in a two-wave mixing scheme. The holographic imaging with multimode lasers results in multiple holograms in the BTO. By employing such lasers the resulting holographic image appears covered of interference fringes corresponding to the object relief and the interferogram spatial frequency is proportional to the diode laser free spectral range (FSR). We used a Fabry-Perot étalon at the laser output for laser mode selection. Thus, larger effective values of the laser FSR were achieved, leading to higher-spatial frequency interferograms and therefore to more sensitive and accurate measurements. The quantitative evaluation of the interferograms was performed through the phase stepping technique (PST) and the phase map unwrapping was carried out through the Cellular-Automata method. For a given surface, shape measurements with different interferogram spatial frequencies were performed and compared, concerning measurement noise and visual inspection.